Korelasi Aktivitas Fisik dan Frekuensi Minuman Manis dengan Kejadian Overweight pada Siswa SMP N 6 Surakarta - Ratu Syifa Auradian; Muwakhidah Muwakhidah; Siti Zulaekah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Overweight among adolescents has become a nutritional issue that continues to grow due to various interrelated factors, including physical activity and the frequency of sugary drink consumption. According to the results of the Indonesian Health Survey (SKI), the proportion of individuals who are overweight reached 16,2%. This study was conducted to analyze the relationship between physical activity and the frequency of sugary drink consumption on the prevalence of overweight among students at SMP Negeri 6 Surakarta. The study employed an analytical observational method using a cross-sectional design, involving 101 students aged 13–15 years, selected through purposive sampling. Physical activity was measured using the Physical Activity Questionnaire for Adolescents (PAQ-A), the frequency of sugary drink consumption was assessed using the Food Frequency Questionnaire (FFQ), and nutritional status was calculated based on BMI-U. All data were then analyzed using Spearman’s rank correlation test. The results showed a prevalence of overweight of 37.63%; the majority of respondents engaged in moderate-intensity physical activity (57,42%) and consumed sugary drinks frequently (48,52%). Based on the Spearman’s rank correlation test, the correlation between physical activity and the incidence of overweight yielded a p-value of 0.408, while the correlation between the frequency of sugary drink consumption and the incidence of overweight yielded a p-value of 0.351; these results indicate that no significant association was found between the two study variables.